An econometric model of Shanghai. - Choo, Chou Foo. (2013)
Shanghai has been China’s largest industrial and commercial city as well as the biggest hub of communications and an important base for science, technology, culture and education. However, it had not been able to take full advantage of its wealth and human resources in China’s reform process in the 1980s. It was only at the start of the 1990s that Shanghai began to make significant progress in re-establishing itself as the commercial, financial and industrial powerhouse of China. In this paper, an econometric model of Shanghai is built so that it can be used as an analytical tool to study certain special features of the Shanghai economy in the areas of foreign trade, inter-regional trade, and central-local relationship.